Typology of organizations in the aspect of corruption counteraction in the Russian Federation - I. A. Damm; V. V. Kostrykina (Russian Journal of Economics and Law)
Objective: to perform typologization of organizations in the aspect of counteracting corruption based on generalization of approaches to understanding organizations and highlighting their types in the system of scientific knowledge.Methods: general scientific method of dialectical cognition, as well as a number of specific scientific methods, such as legal, systemic-structural, formal-logical, etc.Results: a significant obstacle in building a system of corruption counteraction in organizations is the lack of fundamental intersectoral scientific research ranking organizations depending on the degree of influence of their activities on national security. The typologization of organizations in the aspect of corruption counteraction is of great methodological importance, since it allows establishing the basic scientific and practical approaches to ensuring anti-corruption activities, depending on the degree of corruption-related danger of such organizations. Generalization of approaches to the understanding of organizations and the identification of their varieties allowed establishing the dominance of civil law in the knowledge of organizations. At the same time, the classifications of organizations used in this branch of law do not enable to achieve the goal of this study. In this regard, within the framework of this work, the need for interdisciplinary scientific knowledge of the essential characteristics of organizations is actualized, the identification of signs for the typologization of organizations is problematized, and a working typology of organizations in the aspect of combating corruption is proposed. The further scientific cognition of corruption manifestations and mechanisms of their reproduction in the activities of various types of organizations will make it possible to reveal the reserves of anti-corruption activities and provide a systematic multilevel approach in their implementation.Scientific novelty: the paper substantiates the need for typologization of organizations in interconnection with the influence of their corruptiogenity on the security of society and the state to build a multilevel system of counteracting corruption in organizations of various types.Practical significance: the research results can be used in determining the directions for improving state policy in the field of corruption counteraction, as well as anticorruption activity of organizations.